Modifikasi Alat Pengolah Limbah Plastik Menjadi Bahan Bakar Cair Menggunakan Software Solidworks - Laksanawati, Ellysa Kusuma; Lestari, Sri; Muttaqien, Zaenal; Asruri, Tri Asep (Program Studi Teknik Industri Universitas Muhammadiyah Tangerang, 2023)
Plastic is one of the human needs in everyday life, as a place to wrap food and drinks, because plastic is practical, clean, and makes it easy for humans. Plastic is also an artificial inorganic material composed of chemicals that are quite harmful to the environment. To deal with plastic waste, a way is needed, to process the plastic waste into materials that are more useful and also have benefits for nature, one way is by recycling the plastic waste into fuel, namely fuel in the form of oil. By processing plastic waste into fuel oil, besides being able to reduce plastic waste, we can also save petroleum supplies in nature. In addition, the oil produced from this plastic also has a calorific value that is quite high on par with fossil fuels such as gasoline and diesel. The purpose of this research is to create a new tool size and create a new tool design from existing plastic waste processing equipment. The research method that the author uses is a field study method by analyzing existing waste processing equipment into liquid fuel and modifying the tool with Solidworks Software. In modifying the plastic waste processing equipment into liquid fuel, the first step is to modify the frame size which is more compact and not much free space and in modifying the design of the plastic waste processing equipment to become liquid fuel, the design is more attractive and elegant, while also prioritizing safety. Keyword: Oil, Design, Waste, Plastic, Solidworks